Long Waves and Short Waves: Growth Through Intensive and Extensive Search - Jovanovic, Boyan; Rob, Rafael (Econometrica, 1990)
This paper endogenizes the frequency of major discoveries and the extent of their refinement.Four axioms deliver a one-parameter family of beliefs that guide exploratory effort.Such effort trades off the prospect of major new discovery against the chance of successfully refining discoveries made in the past.The only other parameter is the cost of making new discoveries relative to the cost of refining old ones.The paper derives time-series properties of inventive activity as they relate to the two parameters, and it discusses several specific inventions and their subsequent refinement.In doing so, the paper arguably enhances our understanding of the process of discovery.1 We thank the C. V. Starr Center for Applied Economics for technical and financial assistance.The second